KREATIVITAS GURU PAI DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SMAN 2 BERAU KALIMANTAN TIMUR TAHUN PELAJARAN 2024/2025 - Rezab, Muhammad Topik (UNISAN JURNAL, 2025)
This study discusses the creativity of Islamic Education (PAI) teachers in their efforts to enhance student learning motivation at SMAN 2 Berau, East Kalimantan, in the 2024/2025 academic year. The primary focus of this research is to identify the creative techniques applied by PAI teachers and their impact on students’ learning motivation. The research method used is qualitative with a case study approach. Through interviews, observations, and document analysis, the collected data indicate that the use of innovative teaching methods, such as project-based learning and information technology, significantly encourages student interest. As a result, it can be seen that with increased teacher creativity, students’ learning motivation has also significantly improved. This research is expected to provide insights for Islamic education in Indonesia, especially in terms of more interactive and effective teaching. Keywords: Creativity, PAI Teacher, Learning Motivation, Students, Innovative Learning.